Educational Introspections of Medical Students Post Disability Competencies Training: A Qualitative Study - Lonimath, Ashwini; Kannan, Suthanthira; M, Vinaya; R, Deepthi; A, Shivakumar (Indian Journal of Community Health, 2024)
Background: Despite the substantial presence of persons with disabilities (PWD) in the population, they face many barriers in healthcare. Competency-Based Medical Education (CBME) is increasingly used to address these gaps. Aims and Objective: This study assesses the impact of disability competencies training on medical students' attitudes towards PWD. It aims to explore new perspectives, identify attitudinal shifts, evaluate training effectiveness, and promote solution-oriented learning. Materials and Methods: Five Focus Group Discussions (FGD) with 8 participants each, a series of themes related to the understanding of disability and empathy were explored. The participants, who had undergone training in disability competencies. The FGDs were facilitated by trained moderators and analysed employing thematic analysis and generating tree maps. Results: Key themes evolved from the students' new perspectives towards PWD, which included Inclusion and Responsibility, Empathy and Understanding, Managing patients with disabilities, Equity and rights, and Acceptance. Themes also emerged regarding the impact of training, revealing an Attitudinal Shift, Engagement and Interaction, Personal Impact, and Solution-Oriented Learning. Conclusion: Disability competency training significantly transforms medical students' attitudes, fostering a more inclusive, empathetic approach in healthcare. This shift is crucial for integrating disability competencies into medical education, especially in developing countries